2007
DOI: 10.1590/s0102-76382007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Há espaço para o tratamento endovascular nas dissecções crônicas da aorta descendente?

Abstract: Despite the small number of studied patients, the endovascular procedure for chronic type B aortic dissections does not appear to be an option for the treatment of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The false lumen would progressively dilate as a result of a patent re-entry site in the abdominal aorta, and the risk of rupture would persist. A study by Dias et al [ 14 ] in which endovascular treatment was used to treat 11 patients with chronic type B aortic dissections found that although stent-graft deployment was technically successful in all patients false lumen flows persisted in the thorax in 27% of the patients and in the abdomen in 82%, and that aortic diameter was not decreased postoperatively. The authors concluded that endovascular treatment of chronic type B dissections is not effective as it does not decrease aortic diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The false lumen would progressively dilate as a result of a patent re-entry site in the abdominal aorta, and the risk of rupture would persist. A study by Dias et al [ 14 ] in which endovascular treatment was used to treat 11 patients with chronic type B aortic dissections found that although stent-graft deployment was technically successful in all patients false lumen flows persisted in the thorax in 27% of the patients and in the abdomen in 82%, and that aortic diameter was not decreased postoperatively. The authors concluded that endovascular treatment of chronic type B dissections is not effective as it does not decrease aortic diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Lopera et al [ 27 ] , also reported that the presence of reentry at the level of the descending thoracic aorta associated with fibrosis in chronic cases, contribute to the reduced chance of sealing the intimal-middle layer and consequent reduction of thrombosis of the thoracic false lumen. Dias et al [ 28 ] , despite the small number of patients studied, concluded that the endovascular treatment of type B aortic dissection, in the chronic phase, did not decrease the diameter of the descending aorta and showed persistence of the false lumen in the descending segment of the thoracic aorta in 27.3% and abdominal aorta of 81.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular treatment of thoracic aortic diseases has progressed rapidly and led to a reduction in morbidity and mortality when compared to conventional surgery. The procedure is well established to treat descending thoracic and abdominal aorta pathologies [1][2][3][4][5]. However, only a few studies have reported on the treatment of lesions in the ascending aorta (AA) [6,7].…”
Section: Introductionmentioning
confidence: 99%